Study of the Influence PMI Ethical Principles on Software Project Performance Based on the Experiences of Indian Project Managers: Examining the Impact of PMI Ethical Principles on Software Project Performance (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Project management is becoming increasingly common in the workplace, and the world ofinternational business is quickly transforming into a project-oriented culture. Project success is criticalto a company's long-term profitability, yet it is notoriously difficult to accomplish in a variety of sectors.Project managers must continuously walk the delicate line between doing what is right and pleasingeveryone involved. These apparently conflicting viewpoints usually have an ethical grounding. Due tothe rising regularity with which projects fail to provide the value intended, an ethical approach to projectmanagement has been critical in recent years. Researchers and practitioners of project managementlabour ceaselessly to reify ethics in project management, despite the field's expanding importance andintrinsic subjectivity. In the United States, the Project Management Institute (PMI) has developed theProject Management Body of Knowledge (PMBOK) Guide, which is a significant step in this direction.The PMI Code of Ethics and Professional Conduct, as described in the PMBOK, serves as a moraldecision-making framework for project managers. This standard emphasises four elements of ethicsresponsibility, respect, fairness, and honesty. These core principles have served as a global standard forprofessional project management behaviour in all industries.